2020
DOI: 10.31717/2311-8253.20.3.10
|View full text |Cite
|
Sign up to set email alerts
|

Modeling Study of the Atmospheric Transport of Radioactivity Released into the Air as a Result of Forest Fires in the Exclusion Zone in April 2020

Abstract: In April 2020, the largest forest fire occurred in the Chornobyl Exclusion zone in its history. The results of modeling the atmospheric transport of radioactive aerosols raised into the atmosphere as a result of fires in forest and grass areas in the Exclusion zone, as well as in radioactively contaminated forests outside it in Kyiv and Zhytomyr regions are presented in the paper. To assess the consequences of forest fires, a set of models of lifting, atmospheric transport and deposition of radionuclides on th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…1). As Protsak et al [30][31] mentioned, the amount of radionuclides from the surface biomass resuspended into the atmosphere was considered to be limited, because the total burned area in March 2022 was smaller than that of the 2020 wild res, resulting in little or no additional radiation exposure to the public [3][4][5] .…”
Section: Impact Of 2022 Chornobyl Wild Res Compared With Previous Resmentioning
confidence: 99%
See 2 more Smart Citations
“…1). As Protsak et al [30][31] mentioned, the amount of radionuclides from the surface biomass resuspended into the atmosphere was considered to be limited, because the total burned area in March 2022 was smaller than that of the 2020 wild res, resulting in little or no additional radiation exposure to the public [3][4][5] .…”
Section: Impact Of 2022 Chornobyl Wild Res Compared With Previous Resmentioning
confidence: 99%
“…To assess the hazards of air pollution after a large wild re and to relate re severity to changes in land cover, it is important to be able to detect the burned area accurately and rapidly. The amount of radionuclides released into the atmosphere by wild res in the area around Chornobyl can vary greatly depending on the extent to which the res spread 3,4,6,7 , because the radionuclides derived from the Chornobyl accident in the environment are known to be extremely heterogeneous 8-10 . For instance, Igarashi et al 11 found that the inventories of 137 Cs and 90 Sr at two sites located only 5 km apart differ signi cantly, by as much as 13 times and two times, respectively.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, thermal anomalies detected by satellites indicated that in 2020 wildfires in the Chornobyl Exclusion Zone (ChEZ) spread over an extensive area, and satellite images helped to produce an initial estimate that the burned area covered nearly 30% of the ChEZ 1 , 2 . Such information was used to assess the redistribution of radionuclides 3 , 4 and the potential risk of radiation exposure due to the fire and smoke 5 . Satellite images are the only information available for estimating the burned area in case of large wildfires.…”
Section: Introductionmentioning
confidence: 99%
“…To assess the hazards of air pollution after a large wildfire and to relate fire severity to changes in land cover, it is important to be able to detect the burned area accurately and rapidly. The amount of radionuclides released into the atmosphere by wildfires in the area around Chornobyl can vary greatly depending on the extent to which the fires spread 3 , 4 , 6 , 7 , because the radionuclides derived from the Chornobyl accident in the environment are known to be extremely heterogeneous 8 10 . For instance, Igarashi et al .…”
Section: Introductionmentioning
confidence: 99%